Burden and associated characteristics in caregivers of Parkinson's disease patients - Inaltekin, Ali; Kocatürk, Idris (Wiley, 2024)
AbstractBackgroundParkinson's disease (PD) increases patient load and requirements of care. Determining the burden on PD patients' caregivers and associated factors may help to identify methods to reduce caregiver burden. This study investigated the factors associated with caregiver burden among PD patients caregivers.MethodsEighty‐five PD patients and 85 caregivers were included in the study. Zarit Burden Interview (ZBI) was used to measure caregiver burden; the Ways of Coping Scale (WCS) was used for coping; Modified Hoehn‐Yahr Staging (MHYS) was used for staging patients. The International Parkinson and Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) parts 1 and 3 were used to evaluate non‐motor and motor problems. Caregivers' depression and anxiety levels were evaluated with the Beck Depression Inventory and Beck Anxiety Inventory (BAI). Spearmen correlation coefficient was used to evaluate the relationship of variables with the ZBI score, and multiple linear regression analysis was used to determine the predictors of the ZBI score.ResultsA positive significant relationship was found between the ZBI score and BAI score, MHYS score, WCS total score, and subscales: keeping to self, seeking refuge in fate, and seeking refuge in supernatural forces. MHYS score, WCS total score, BAI score, and MDS‐UPDRS‐1 were predictors of the ZBI score.ConclusionsThe anxiety levels of caregivers, their ways of coping, and the patient's stage of the disease are important in caregiver burden. Coping ways can be changed to reduce the care burden. Developing psychological interventions for caregivers to change their coping styles can be important.
Keywords: Male; Psychiatric Status Rating Scales; Adult; Depression; Caregiver Burden; Parkinson Disease; Middle Aged; Anxiety; Severity of Illness Index; Cross-Sectional Studies; Caregivers; Cost of Illness; Surveys and Questionnaires; Adaptation, Psychological; Humans; Female; Aged